2020
DOI: 10.1128/mcb.00470-19
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 27a Is a Key Modulator of Cholesterol Biosynthesis

Abstract: Hypercholesterolemia is a strong predictor of cardiovascular diseases. The 3-hydroxy-3-methylglutaryl coenzyme A reductase gene (Hmgcr) coding for the rate-limiting enzyme in the cholesterol biosynthesis pathway is a crucial regulator of plasma cholesterol levels. However, the posttranscriptional regulation of Hmgcr remains poorly understood. The main objective of this study was to explore the role of microRNAs (miRNAs) in the regulation of Hmgcr expression. Systematic in silico predictions and experimental an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…3 A and Additional file 1 : S2A). In some cases, two bands of HMGCR have been detected in our and other studies [ 32 , 33 ]. The upper one is the HMGCR band and the lower one is the non-specific band.…”
Section: Resultssupporting
confidence: 71%
“…3 A and Additional file 1 : S2A). In some cases, two bands of HMGCR have been detected in our and other studies [ 32 , 33 ]. The upper one is the HMGCR band and the lower one is the non-specific band.…”
Section: Resultssupporting
confidence: 71%
“…Moreover, it was observed that hypoxia, a sign of liver damage, induced binding of early growth response protein 1 (Egr1) to promoter regions of miR-27a, leading to its induction, to mediate the downregulation of HMGCR. Finally, increase of miR-27a and decrease of HMGCR were found in livers of three mice models of MetS [334]. Further, C57BL/6J mice with diet-induced hypercholesterolemia showed also amelioration of hypercholesterolemia, yet upon delivery of miR-30c mimic to the liver due to decrease of hepatic lipoprotein production but not LDL clearance [335].…”
Section: Microrna In Mets-a Link With Chronic Inflammation Related Tomentioning
confidence: 95%
“…Other miRNAs implicated in potential therapy of hypercholesterolemia are miR-27a and miR-30c. First of them was injected via tail vein into Apoe-/-mice subjected to high cholesterol diet and suggested to diminish plasma lipid levels along with hepatic levels of HMGCR [334]. Further, miR-27a was proved to directly target HMGCR via translational repression and mRNA decay.…”
Section: Microrna In Mets-a Link With Chronic Inflammation Related Tomentioning
confidence: 99%
“…miRNA-122, present mainly in hepatocytes, when inhibited significantly suppresses blood cholesterol level ( Rotllan and Fernandez-Hernando, 2012 ). miR-27a has been shown to control HMGCR level either by a posttranslational block or by mRNA degradation ( Khan et al, 2020 ). Strikingly, other miRNAs have been discovered by meta-analyses to be associated with cholesterol–lipoprotein trafficking alterations, such as miR-128-1, miR-148a, miR-130b, and miR-301b.…”
Section: Cholesterol Metabolismmentioning
confidence: 99%
“…miR-27a has been shown to control HMGCR level either by a posttranslational block or by mRNA degradation (Khan et al, 2020). Strikingly, other miRNAs have been discovered by meta-analyses to be associated with cholesterol-lipoprotein trafficking alterations, such as miR-128-1, miR-148a, miR-130b, and miR-301b.…”
Section: Introductionmentioning
confidence: 99%